Iron Carbide Nanoparticles Encapsulated in Mesoporous Fe‐N‐Doped Carbon Nanofibers for Efficient Electrocatalysis1. (26th May 2015) - Wu, Zhen‐Yu; Xu, Xing‐Xing; Hu, Bi‐Cheng; Liang, Hai‐Wei; Lin, Yue; Chen, Li‐Feng; Yu, Shu‐Hong
Abstract Exploring low‐cost and high‐performance nonprecious metal catalysts (NPMCs) for oxygen reduction reaction (ORR) in fuel cells and metal–air batteries is crucial for the commercialization of these energy conversion and storage devices. Here we report a novel NPMC consisting of Fe3C nanoparticles encapsulated in mesoporous Fe‐N‐doped carbon nanofibers, which is synthesized by a cost‐effective method using carbonaceous nanofibers, pyrrole, and FeCl3 as precursors. The electrocatalyst exhibits outstanding ORR activity (onset potential of −0.02 V and half‐wave potential of −0.140 V) closely comparable to the state‐of‐the‐art Pt/C catalyst in alkaline media, and good ORR activity in acidic media, which is among the highest reported activities of NPMCs.